PWE-064 The clinical outcomes of a personalised approach to the management of patients taking thiopurine medication, using metabolite assessments. (22nd June 2015) - Leyland, R; Price, T; Lithgo, K; Housley, D; Johnson, MW
Abstract : Introduction: A significant number of patients with inflammatory bowel disease (IBD) are treated with thiopurine drugs. Typically patients are commenced on starting doses of Azathioprine (AZA) or 6-Mercaptopurine (6-MP) and these are titrated up to 2.5 mg/kg and 1.25 mg/kg respectively, provided this is tolerated. Measurement of thiopurine metabolites (TPM), 6-Thioguanine nucleotide (6-TGN) and 6-Methylmercaptopurine nucleotide (6-MMPN), has proved useful in improving therapeutic efficacy, minimising unwanted side effects and identifying non-compliance. The aim of this study was to use TPM analysis to help guide the management of patients within our immunomodulator service, at the Luton and Dunstable University Hospital, taking thiopurine drugs. Method: The gastroenterology department identified 406 patients with IBD who were taking thiopurine drugs. Letters were sent out on mass to these patients in December 2014 requesting a blood test for TPM before the end of January 2015. The patient's samples were sent to Birmingham City Hospital for measurement of 6-TGN and 6-MMPN. A thiopurine management algorithm was designed to help clinicians understand these TPMs and direct them on how best to act on these results. Results: Of the 406 patients who were sent TPM test requests, 200 attended prior to the end of January. These included 156 patients taking AZA and 44 taking 6-MP. The results for 6-TGN and 6-MMPN determined a change in management for 124 patients (62%), with only 76 patients (38%) classified as having an 'accurate dose' of AZA or 6-MP. Non-compliance with thiopurine therapy was evident for 15 patients (7.5%), and a further 5 patients phoned the IBD nurses directly admitting non-compliance. The dose of AZA or 6-MP was increased for 28 patients (14%) and decreased for 71 patients (35.5%). Thiopurine therapy was stopped in 10 patients (5%) due to significantly high levels of 6-TGN or 6-MMPN. A number of patients were classified as being 'too sensitive' to the thiopurine drugs with high concentrations of 6-MMPN. Based on the results of 6-TGN and 6-MMPN the drug used by 1 patient was changed from AZA to 6-MP. Conclusion: The assessment of thiopurine metabolites directly led to the dose adjustment of AZA and 6-MP in 62% of patients tested. The measurement of 6-TGN and 6-MMPN enables appropriate personalised thiopurine dosing, following a simple thiopurine management algorithm, to optimise their therapy. Non-compliance is easy to identify and patients who preferentially metabolise thiopurine drugs to the hepatotoxic metabolite 6-MMPN had their therapy stopped, enabling initiation of alternative treatment modalities. Further work would be necessary to assess whether this reduces complications in the long term. Disclosure of interest: None Declared.